2009
DOI: 10.1002/ange.200905591
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Isostructural Main‐Chain Modifications for the Design of Antimicrobial Foldamers: Helical Mimics of Host‐Defense Peptides Based on a Heterogeneous Amide/Urea Backbone

Abstract: Wie Zwillinge: Oligoharnstoffe und γ‐Peptide sind isostere und quasi‐isostrukturelle helicale Foldamere mit besonderen Eigenschaften bei der biomolekularen Erkennung. Die Kombination dieser beiden Rückgrate in Harnstoff‐Amid‐Hybriden (siehe Bild) ergab wirksamere antimikrobielle helicale Foldamere mit verminderter Cytotoxizität.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 22 publications
(12 reference statements)
3
58
0
Order By: Relevance
“…37 The quest to overcome these challenges posed by innate HDPs has fueled the search for biomimetic oligomers over the past two decades. These oligomeric peptidomimetics such as β-peptides, 6,3840 peptoids, 10,31,4147 arylamide oligomers, 48 β-turn mimetics, 49,50 and others 12 have been able to proffer solutions to the problems mentioned above because of their unnatural backbone. Inspired by these findings, we have designed and investigated a few types of antimicrobial AApeptides.…”
Section: Function Of Aapeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The quest to overcome these challenges posed by innate HDPs has fueled the search for biomimetic oligomers over the past two decades. These oligomeric peptidomimetics such as β-peptides, 6,3840 peptoids, 10,31,4147 arylamide oligomers, 48 β-turn mimetics, 49,50 and others 12 have been able to proffer solutions to the problems mentioned above because of their unnatural backbone. Inspired by these findings, we have designed and investigated a few types of antimicrobial AApeptides.…”
Section: Function Of Aapeptidesmentioning
confidence: 99%
“…γ-AA7 and γ-AA8 (Figure 9), with the same charge distribution and hydrophobicity, were the most potent antimicrobial sulfono-γ-AApeptides in the library (Table 2). 12,45,73,74 Small-angle X-ray scattering (SAXS) showed that γ-AA8 is less helical than γ-AA7 , suggesting N-terminal acetylation has significant effects on folding. Interestingly, γ-AA8 showed antimicrobial activity that was better than that of γ-AA7 and is less hemolytic and cytotoxic to mammalian cells than γ-AA7 is.…”
Section: Function Of Aapeptidesmentioning
confidence: 99%
“…27 These structural features have also proven to be important in conferring antimicrobial activity on peptidomimetic oligomers 3541 and polymers, 4247 including β-peptide-based structures composed, either entirely or in part, of β-amino acid residues. 48,49 Owing to their folding principles, structural diversity, secondary structure stability, 50,51 and resistance to proteolysis, 52 β-peptides represent a promising class of compounds to elucidate mechanisms of AMP activity and to template development of new antifungal therapeutics.…”
mentioning
confidence: 99%
“…Please do not adjust margins 3 were measured with an Agilent Supernova diffractometer using an Agilent Eos CCD detector. The structures were solved with direct methods and refined using Fourier techniques.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…1,2 Foldamers are generally considered as artificial models for molecular folding, 3 but they may also find use in enzyme-like functions, for example as biomimetic receptors 4 and catalysts 5,6,7 . The most common bond type in foldamers is the amide bond with directional and relatively stable hydrogen bonding properties.…”
Section: Introductionmentioning
confidence: 99%